EUTHANASIA DITINJAU DARI HUKUM PIDANA DI INDONESIA - Ramanata Disurya (Justici, 2020)
Abstract The emergence of pros and cons around the issue of euthanasia becomes a burden for law experts. Because, on the issue of "legality" this euthanasia issue will end. This study aims to see how Euthanasia is viewed from the perspective of criminal law in Indonesia. This research is a type of legal research which is also referred to as empirical legal research. The results of this study are in the criminal law in force in Indonesia which regulates the issue of euthanasia contained in Article 304 of the Criminal Code which prohibits the existence of passive euthanasia, and in Article 344 of the Criminal Code which prohibits the existence of active euthanasia. So that euthanasia is an act that cannot be applied or has not been legalized because it is contrary to the Criminal Code (KUHP)